Re-imagining Broadcasting in the Public Interest. SABC TV Broadcasting in a Commercialised Competitive Media System - Momelezi Kula; Maud Blose (Communicare)
The article looks at the South African Broadcasting Corporation as a case study to examine the impact of liberalisation and competition by examining scheduling and programming to ascertain diversity. The public sphere theory was used to evaluate its performance as a public service broadcaster. The article challenges the arguments that, first, liberalisation commercialises public service broadcasting which results in the erosion of the public sphere through excessive similarity in programming, thus excluding certain perspectives, fragmenting audiences and limiting its social and integrative role. Second, commercial interests have undermined the service mandate of public service broadcasting and it has lost legitimacy and relevance. It also decries the dominance of public service broadcasting literature from the North, which focuses on the public‒private dichotomous approach that emphasises collective interest over personal choice, and commonality over diversity. Findings show that the South African Broadcasting Corporation's programming is diverse with high local content, and that responses to competition are not deterministic, while commercialisation and convergence are inherent risks that can be mitigated by creative programming strategies and regulation. Findings further provide insight into the approach of the South African Broadcasting Corporation to scheduling and programming through broadcasting the rainbow nation, a construct that suggests ideals of nation building, unity and diversity as public interest embedded in the broadcasting legislative and organisational frameworks. The notion of the rainbow nation is rooted in diverse cultures and the different racial makeup of South Africa.